Case Report: Successful Repair of Primary Aortoesophageal Fistula With an Endovascular Stent Graft and an Esophageal Stent - Wu, Zhi-Wei; Yao, Yong-Dong; Li, Yi-Ming (Frontiers in Surgery, 2022)
Aortoesophageal fistula (AEF) secondary to thoracic pseudoaneurysm as a result of upper gastrointestinal bleeding is a rare condition and will be undoubtedly lethal if without prompt surgical intervention. The estimated annual incidence of primary AEFs and secondary AEFs is about 0.0015% and 0.6-2% respectively. The challenges of the therapy posed by AEF are control of the hemorrhage, arterial reconstruction in an infection field, control of sepsis and re-establishment of the alimentary tract. We present a case of a 58-year-old man who suffered from chest pain and hematemesis and finally diagnosed as pAEF caused by descending thoracic pseudoaneurysm. Our team successfully deployed an endovascular stent-graft and esophageal stent to seal ruptured thoracic aorta and esophageal defect, which provided a new surgical strategy for aortoesophageal fistula in the endovascular era.